Some mulochases on the study of the living regions of the early settlers of Central Asia on the basis of material resources - Shavkat Safaralievich Amonturdiev; Nezavisimi Issledovatel Termezskogo (Peerian Journals Publishing, 2022)
in the article, the author spoke about the stages of development in the nomadic peoples of Central Asia until the emergence of the first "political associations" and the emergence of statehood, the regions of residence of these tribes, the identified settlements and archaeological research on them.
Keywords: nomadic peoples of Central Asia; sacs; massagets; settlements of nomadic tribes